Active Basalt Alteration at Supercritical Conditions in a Seawater-Recharged Hydrothermal System: IDDP-2 Drill Hole, Reykjanes, Iceland - Zierenberg, Robert; Fridleifsson, Gudmunduer; Elders, Wilfred; Schiffman, Peter; Fowler, Andrew (Zenodo, 2021)
The 4.5 km deep IDDP-2 drill hole was drilled at Reykjanes, Iceland, in an active seawater-recharged hydrothermal system on the landward extension the Mid-Atlantic Ridge. Drilling targeted a well-defined hydrothermal up-flow zone feeding the Reykjanes geothermal reservoir, which produces fluids compositionally equivalent to basalt-hosted deep sea hydrothermal vents. Spot cores recovered from depths between 3648 to 4659 meters depths consist of pervasively altered sheeted diabase dikes. The shallowest core has an alteration mineral assemblage similar to the producing geothermal reservoir but is being overprinted by the underlying Hornblende Zone assemblage dominated by labradorite and hornblende. The deepest cored section (4634-4659 m) retains a diabasic texture, but all primary minerals are replaced or have changed composition. Plagioclase ranges from An 30 to An 99 and igneous augite is replaced by intergrown hornblende, clinopyroxene, and orthopyroxene. Hydrothermal biotite and potassium feldspar formed locally due to reaction with a phase-separated brine, indicated by co-existing vapor-rich and salt + vapor-rich fluid inclusions. Seawater-derived supercritical hydrothermal fluid entering the bottom of the bore hole actively phase separates due pressure drop controlled by the fluid levels in the drill hole. Felsic veins, present in trace amounts, record a continuous transition from magmatic to hydrothermal conditions, including incipient hydrous melting. The vertical changes observed in mineralogy and mineral chemistry indicate that fluids from the deep high temperature reaction zone can undergo significant cooling and reaction with host rocks along their path to the seafloor.